CONTRIBUTION TO THE LEAF LITTER FUNGI FROM MAHARASHTRA-II - S. D. PATIL, M. S. PATlL, U. S. YADAV AND (Indian Phytopathology, 2002)
Codinaea Maire has been described with its six species, viz., C. falcatispora sp. nov., C. fruticola sp. nov., Codinaea state of Chaetosphaeria callimorpha (Mont.) Sacc., C. hughesii Ellis, C. ixorae sp. novo and C. selosa Hughes and Kendrick. Out of these taxa, three are new species and remaining three constitute new records in India. In view of the present additions, a key to the Indian species is given.